Association of bodily discomfort with occupational risk factors in poultry slaughterhouse workers (2017)
Brazil is classified as the second largest world chicken meat producer and leading exporter. This study aimed at analyzing the characteristics of bodily discomfort in poultry slaughterhouse workers, and its associations with the occupational risk factors. The study included 312 workers, 207 females and 105 males. A body map for evaluating discomfort and an interview regarding organizational issues and criteria of the OCRA method were used. Descriptive statistics and Chi-square test (p≤0.05) were used. It was found that 85.9% of respondents performed repetitive tasks, 98.1% took rest breaks, 44.6% performed job rotation (2-7 tasks), 40.4% used tools and 62.5% felt cold. Additionally, 71.2% felt discomfort in at least one body region and the body regions most frequently cited were shoulders (50.3%) and arms (34.3%). There was association between body discomfort and individuals’ sex (p0.001), task characteristics (repetitive and non-repetitive) (p=0.001), use of tools (p=0.008) and perception of cold (p0.001).